Quantitative study of oil-to-bunch ratio of unripe oil palm Fresh Fruit Bunches (FFB) / Haziq Nor Azahar - Nor Azahar, Haziq (Faculty of Plantation and Agrotechnology, 2017)
Malaysia is now the second largest producer of palm oil in the world that needs more emphasis on its research and development to meet the world challenge. One of the major issues is abundance of unripe fresh fruit bunches (FFB) in palm oil mill that caused by harvester mistakes which can lead environmental pollution and also losses to the palm oil industry. A study was conducted at Sime Darby Kempas Palm Oil Mill Jasin to determine percentage of oil content in unripe FFB according to different sizes (small <13 kg, medium 13-18 kg, and large >18 kg) and to compare the results with the ripe FFB. Bunch analysis procedure was used to determine the percentage of oil content of unripe FFB. The result showed that, there was no significant different between the percentage of oil content in different sizes of unripe FFB. The percentage of oil content in unripe FFB of different sizes is 14.94%-15.95% and this showed that unripe FFB has lower percentage of oil content than ripe FFB for the comparison. For economic analysis, from 10% of unripe FFB discarded at the palm oil mill per day, 15 tonnes crude palm oil (CPO) can be produced and at least RM42,000 losses of oil occurred per day. This study concludes the unripe FFB must be processed because it still can generate profits. In conclusion, this study will give many benefit in term of generate profit, avoid losses and avoid wasting unripe FFB. In future, study about technology used should be carried out to find suitable method to process unripe FFB.